DETERMINATION OF ENERGY SAVING METHODS IN THE PROCESSING OF HYDROCARBON GASES - Yuldashev Xusan Makhmudovich; Islomov Alisher Nurillayevich; Egamnazarovna Fazilat Dustkobilovna (Galaxy International Interdisciplinary Research Journal, 2021)
This article discusses ways to achieve energy efficiency with internal and external energy savings in the processing and preparation of hydrocarbon gases, as well as energy efficiency devices that depend on the composition of the equipment and the operating mode of the power complex. as energy saving in industrial enterprises. Information on measures to optimize the operating mode of technological units, methods of using secondary fuel and energy resources.